Analyzing Purchase Decision Process Online Shopping in Islamic Shari’a Perspective - W. Sakti, Intan; Hurriyati, Ratih (International Journal of Psychosocial Rehabilitation, 2020)
Online shopping has grown exponentially because of the technology. Thus, we can see in all aspects, whether in economics, growth country, or demographic features. This study highlights purchase decision processes in online shopping that focused on Islamic material. Significant growth of how to sell is having a vast demand, which is why retailers and online shops began priority ways to buy products, and this way is giving a big chance for the growth country also. Analyzing this process will reveal how shari’a the business online shop from an Islamic point of view also in marketing knowledge.